2018
DOI: 10.1080/23294515.2018.1510437
|View full text |Cite
|
Sign up to set email alerts
|

Reliance agreements and single IRB review of multisite research: Concerns of IRB members and staff

Abstract: The new National Institutes of Health (NIH) Policy on the Use of a Single Institutional Review Board (sIRB) for Multi-Site Research was adopted primarily to simplify and speed the review of complex multisite clinical trials. However, speeding review requires overcoming a number of obstacles. Perhaps the most substantial obstacle is the time and effort needed to develop reliance agreements among the participating sites. We conducted 102 semistructured interviews with sIRB personnel, including directors, chairs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Several commercial single IRB administrators expressed interest in participating but reported that they first needed permission from their companies' owners, who then refused, citing a lack of any financial or other business advantages to be gained from participation. Of these single IRBs, 25% (5) and 75% (15) reviewed high and low annual volumes of protocols, respectively; and 30% (6) reviewed protocols only about certain specific diseases, while 70% (14) did not.…”
Section: E R H E R Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Several commercial single IRB administrators expressed interest in participating but reported that they first needed permission from their companies' owners, who then refused, citing a lack of any financial or other business advantages to be gained from participation. Of these single IRBs, 25% (5) and 75% (15) reviewed high and low annual volumes of protocols, respectively; and 30% (6) reviewed protocols only about certain specific diseases, while 70% (14) did not.…”
Section: E R H E R Hmentioning
confidence: 99%
“…This single IRB approach aims to increase the efficiency of IRB review of multisite research without jeopardizing protections for research subjects. 5 Here we report findings about single IRBs' willingness or unwillingness to participate in research that investigates how they function. In previous publications, we reported findings about how single IRBs address issues about conflicts of interest, 3 local knowledge, 4 and reliance agreements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for multicenter trials with problems, such as increased cost or duplication of decisions, a single IRB with standard review templates is suggested (Ervin et al, 2016, Resnik et al, 2018. For more reliable IRB review of SAE reporting during multisite studies, a well-structured and standardized form containing sufficient and precise SAE and participant details should be continuously developed (Lidz et al, 2018). Many have criticized IRBs' ongoing safety surveillance during clinical trials, such as the appropriateness of board members' professional background and experience for them to determine potentially critical and serious issues in clinical trials (Morse et al, 2001;Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Especially for multicenter trials with problems, such as increased cost or duplication of decisions, a single IRB with standard review templates is suggested (Ervin et al, 2016, Resnik et al, 2018). For more reliable IRB review of SAE reporting during multisite studies, a well-structured and standardized form containing sufficient and precise SAE and participant details should be continuously developed (Lidz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%